Unravelling 2-oxoglutarate turnover and substrate oxidation dynamics in 5-methylcytosine-oxidising TET enzymes - Klemensas Šimelis; Roman Belle; Akane Kawamura (Communications Chemistry)
Abstract Fe(II)- and 2-oxoglutarate (2OG)-dependent dioxygenases use 2OG and O2 cofactors to catalyse substrate oxidation and yield oxidised product, succinate, and CO2. Simultaneous detection of substrate and cofactors is difficult, contributing to a poor understanding of the dynamics between substrate oxidation and 2OG decarboxylation activities. Here, we profile 5-methylcytosine (5mC)-oxidising Ten-Eleven Translocation (TET) enzymes using MS and 1H NMR spectroscopy methods and reveal a high degree of substrate oxidation-independent 2OG turnover under a range of conditions. 2OG decarboxylase activity is substantial (>20% 2OG turned over after 1 h) in the absence of substrate, while, under substrate-saturating conditions, half of total 2OG consumption is uncoupled from substrate oxidation. 2OG kinetics are affected by substrate and non-substrate DNA oligomers, and the sequence-agnostic effects are observed in amoeboflagellate Naegleria gruberi NgTet1 and human TET2. TET inhibitors also alter uncoupled 2OG kinetics, highlighting the potential effect of 2OG dioxygenase inhibitors on the intracellular balance of 2OG/succinate.